Accounting for space-quantification of cell-to-cell transmission kinetics using virus dynamics models - Kumberger, Peter; Durso-Cain, Karina; Uprichard, Susan L.; Dahari, Harel; Graw, Frederik (Viruses, 2018)
Mathematical models based on ordinary differential equations (ODE) that describe the population dynamics of viruses and infected cells have been an essential tool to characterize and quantify viral infection dynamics. Although an important aspect of viral infection is the dynamics of viral spread, which includes transmission by cell-free virions and direct cell-to-cell transmission, models used so far ignored cell-to-cell transmission completely, or accounted for this process by simple mass-action kinetics between infected and uninfected cells. In this study, we show that the simple mass-action approach falls short when describing viral spread in a spatially-defined environment. Using simulated data, we present a model extension that allows correct quantification of cell-to-cell transmission dynamics within a monolayer of cells. By considering the decreasing proportion of cells that can contribute to cell-to-cell spread with progressing infection, our extension accounts for the transmission dynamics on a single cell level while still remaining applicable to standard population-based experimental measurements. While the ability to infer the proportion of cells infected by either of the transmission modes depends on the viral diffusion rate, the improved estimates obtained using our novel approach emphasize the need to correctly account for spatial aspects when analyzing viral spread.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Cell-to-cell transmission; Mathematical modeling; Spatial effects; Virus dynamics

Agent-based and phylogenetic analyses reveal how HIV-1 moves between risk groups: Injecting drug users sustain the heterosexual epidemic in Latvia - Graw, Frederik; Leitner, Thomas; Ribeiro, Ruy M. (Epidemics, 2012)
Injecting drug users (IDUs) are a driving force for the spread of HIV-1 in Latvia and other Baltic States, accounting for a majority of cases. However, in recent years, heterosexual cases have increased disproportionately. It is unclear how the changes in incidence patterns in Latvia can be explained, and how important IDUs are for the heterosexual sub-epidemic. We introduce a novel epidemic model and use phylogenetic analyses in parallel to examine the spread of HIV-1 in Latvia between 1987 and 2010. Using a hybrid framework with a mean-field description for the susceptible population and an agent-based model for the infecteds, we track infected individuals and follow transmission histories dynamically formed during the simulation.The agent-based simulations and the phylogenetic analysis show that more than half of the heterosexual transmissions in Latvia were caused by IDU, which sustain the heterosexual epidemic. Indeed, we find that heterosexual clusters are characterized by short transmission chains with up to 63% of the chains dying out after the first introduction. In the simulations, the distribution of transmission chain sizes follows a power law distribution, which is confirmed by the phylogenetic data. Our models indicate that frequent introductions reduced the extinction probability of an autonomously spreading heterosexual HIV-1 epidemic, which now has the potential to dominate the spread of the overall epidemic in the future. Furthermore, our model shows that social heterogeneity of the susceptible population can explain the shift in HIV-1 incidence in Latvia over the course of the epidemic. Thus, the decrease in IDU incidence may be due to local heterogeneities in transmission, rather than the implementation of control measures. Increases in susceptibles, through social or geographic movement of IDU, could lead to a boost in HIV-1 infections in this risk group. Targeting individuals that bridge social groups would help prevent further spread of the epidemic. © 2012 Elsevier B.V.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Agent-based model; Evolution; Phylodynamics; Social structure; Transmission chain

A Hepatitis C virus genotype 1b posttransplant isolate with high replication efficiency in cell culture and its adaptation to infectious virus production in vitro and in vivo - Heuss, Christian; Rothhaar, Paul; Burm, Rani; Lee, Ji Young; Ralfs, Philipp; Haselmann, Uta; Ströh, Luisa J.; Colasanti, Ombretta; Tran, Cong Si; Schäfer, Noemi; Schnitzler, Paul; Merle, Uta; et al. (PLoS Pathogens, 2022)
Hepatitis C virus (HCV) is highly diverse and grouped into eight genotypes (gts). Infectious cell culture models are limited to a few subtypes and isolates, hampering the development of prophylactic vaccines. A consensus gt1b genome (termed GLT1) was generated from an HCV infected liver-transplanted patient. GLT1 replicated to an outstanding efficiency in Huh7 cells upon SEC14L2 expression, by use of replication enhancing mutations or with a previously developed inhibitor-based regimen. RNA replication levels almost reached JFH- 1, but full-length genomes failed to produce detectable amounts of infectious virus. Longterm passaging led to the adaptation of a genome carrying 21 mutations and concomitant production of high levels of transmissible infectivity (GLT1cc). During the adaptation, GLT1 spread in the culture even in absence of detectable amounts of free virus, likely due to cellto- cell transmission, which appeared to substantially contribute to spreading of other isolates as well. Mechanistically, genome replication and particle production efficiency were enhanced by adaptation, while cell entry competence of HCV pseudoparticles was not affected. Furthermore, GLT1cc retained the ability to replicate in human liver chimeric mice, which was critically dependent on a mutation in domain 3 of nonstructural protein NS5A. Over the course of infection, only one mutation in the surface glycoprotein E2 consistently reverted to wildtype, facilitating assembly in cell culture but potentially affecting CD81 interaction in vivo. Overall, GLT1cc is an efficient gt1b infectious cell culture model, paving the road to a rationale-based establishment of new infectious HCV isolates and represents an important novel tool for the development of prophylactic HCV vaccines.
CRIS-Team Scopus Importer:2022-12-14

A wall-time minimizing parallelization strategy for approximate Bayesian computation - Alamoudi, Emad; Reck, Felipe; Bundgaard, Nils; Graw, Frederik; Brusch, Lutz; Hasenauer, Jan; Schälte, Yannik (PLoS ONE, 2024)
Approximate Bayesian Computation (ABC) is a widely applicable and popular approach to estimating unknown parameters of mechanistic models. As ABC analyses are computationally expensive, parallelization on high-performance infrastructure is often necessary. However, the existing parallelization strategies leave computing resources unused at times and thus do not optimally leverage them yet. We present look-ahead scheduling, a wall-time minimizing parallelization strategy for ABC Sequential Monte Carlo algorithms, which avoids idle times of computing units by preemptive sampling of subsequent generations. This allows to utilize all available resources. The strategy can be integrated with e.g. adaptive distance function and summary statistic selection schemes, which is essential in practice. Our key contribution is the theoretical assessment of the strategy of preemptive sampling and the proof of unbiasedness. Complementary, we provide an implementation and evaluate the strategy on different problems and numbers of parallel cores, showing speed-ups of typically 10-20% and up to 50% compared to the best established approach, with some variability. Thus, the proposed strategy allows to improve the cost and run-time efficiency of ABC methods on high-performance infrastructure.
CRIS-Team Scopus Importer:2024-03-08

Can Non-lytic CD8+ T Cells Drive HIV-1 Escape? - Al Basatena, Nafisa-Katrin Seich; Chatzimichalis, Konstantinos; Graw, Frederik; Frost, Simon D. W.; Regoes, Roland R.; Asquith, Becca (PLoS Pathogens, 2013)
The CD8+ T cell effector mechanisms that mediate control of HIV-1 and SIV infections remain poorly understood. Recent work suggests that the mechanism may be primarily non-lytic. This is in apparent conflict with the observation that SIV and HIV-1 variants that escape CD8+ T cell surveillance are frequently selected. Whilst it is clear that a variant that has escaped a lytic response can have a fitness advantage compared to the wild-type, it is less obvious that this holds in the face of non-lytic control where both wild-type and variant infected cells would be affected by soluble factors. In particular, the high motility of T cells in lymphoid tissue would be expected to rapidly destroy local effects making selection of escape variants by non-lytic responses unlikely. The observation of frequent HIV-1 and SIV escape poses a number of questions. Most importantly, is the consistent observation of viral escape proof that HIV-1- and SIV-specific CD8+ T cells lyse infected cells or can this also be the result of non-lytic control? Additionally, the rate at which a variant strain escapes a lytic CD8+ T cell response is related to the strength of the response. Is the same relationship true for a non-lytic response? Finally, the potential anti-viral control mediated by non-lytic mechanisms compared to lytic mechanisms is unknown. These questions cannot be addressed with current experimental techniques nor with the standard mathematical models. Instead we have developed a 3D cellular automaton model of HIV-1 which captures spatial and temporal dynamics. The model reproduces in vivo HIV-1 dynamics at the cellular and population level. Using this model we demonstrate that non-lytic effector mechanisms can select for escape variants but that outgrowth of the variant is slower and less frequent than from a lytic response so that non-lytic responses can potentially offer more durable control.
CRIS-Team Scopus Importer:2022-12-14

CD8+ T cells are activated in an antigen-independent manner in HIV-infected individuals - Bastidas, Sonia; Graw, Frederik; Smith, Miranda Z.; Kuster, Herbert; Guenthard, Huldrych F.; Oxenius, Annette (Journal of Immunology, 2014)
Hyperactivation of T cells, particularly of CD8+ T cells, is a hallmark of chronic HIV 1 (HIV-1) infection. Little is known about the antigenic specificities and the mechanisms by which HIV-1 causes activation of CD8 + T cells during chronic infection. We report that CD8+ T cells were activated during in vivo HIV-1 replication irrespective of their Ag specificity. Cytokines present during untreated HIV-1 infection, most prominently IL-15, triggered proliferation and expression of activation markers in CD8+ T cells, but not CD4+ T cells, in the absence of TCR stimulation. Moreover, LPS or HIV-1-activated dendritic cells (DCs) stimulated CD8+ T cells in an IL-15-dependent but Ag-independent manner, and IL-15 expression was highly increased in DCs isolated from viremic HIV-1 patients, suggesting that CD8+ T cells are activated by inflammatory cytokines in untreated HIV-1 patients independent of Ag specificity. This finding contrasts with CD4+ T cells whose in vivo activation seems biased toward specificities for persistent Ags. These observations explain the higher abundance of activated CD8+ T cells compared with CD4+ T cells in untreated HIV-1 infection. Copyright © 2014 by The American Association of Immunologists, Inc.
CRIS-Team Scopus Importer:2022-12-14

Combined treatment and prevention strategies for hepatitis C virus elimination in the prisons in New South Wales: a modelling study - Bretana, Neil A.; Gray, Richard R.; Cunningham, Evan B.; Betz-Stablein, Brigid; Ribeiro, Ruy; Graw, Frederik; Luciani, Fabio; Lloyd, Andrew R. (Addiction, 2020)
Background and aims: Australia is currently on track to meet the World Health Organization (WHO) global hepatitis C virus (HCV) elimination goals by 2030, reflecting universal subsidized access to testing and direct-acting antiviral (DAA) treatment. In New South Wales, DAA treatment in prisons has scaled-up substantially, with 1000 prisoners treated in 2017. However, HCV prevalence and incidence in this setting is high, which could undermine elimination efforts. This study aimed to test the preventative effects of DAA treatment scale-up, opiate substitution treatment (OST) and needle and syringe programme (NSP) strategies for prisons. Design: Modelling study using an individual-based mathematical model of a typical prison setting. The model was calibrated against Australian epidemiological data sets and executed in-prison events for each individual daily, including movements between prisons, changes in risk behaviour and uptake of prevention measures such as OST and NSP, as well as DAA treatment. Scenarios were projected from 2018 to 2030. Setting: New South Wales prisons. Participants: New South Wales prisoners. Measurements: Variables including prison populations, prevalence and incidence rate were calculated. Prisoners were described by demographic characteristics, HCV infection history, risk behaviours and accessing treatment and prevention measures in varied security settings. Findings: Increasing the number of prisoners treated for HCV to 2000 annually was projected to reduce the HCV incidence rate to 8.69 [95% confidence interval (CI) = 8.17, 9.20] per 100 person-years (100 p.y.). Combined treatment and prevention strategies were necessary to reduce the projected incidence rate to 5.22 (95% CI = 5.13, 5.52) per 100 p.y. Considering the expected reductions in the prevalence of chronic HCV in the Australian community, incidence rate was predicted to drop to 0.93 (95% CI = 0.92, 0.98) per 100 p.y. by 2030. Conclusions: This model, which simulates prison scenarios to inform Australia's national hepatitis C virus elimination efforts, suggests that continued direct-acting antiviral (coverage in the community combined with a moderate increase of direct-acting antiviral treatments in prisons, and introduction of improved harm reduction via opiate substitution treatment and/or needle and syringe programmes, makes hepatitis C virus elimination feasible in Australian prisons.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Direct-acting antiviral; HCV; hepatitis C virus; modelling; needle and syringe exchange programme; prevention; prisons; treatment

Comparison of cytotoxic T lymphocyte efficacy in acute and persistent lymphocytic choriomeningitis virus infection - Graw, Frederik; Richter, Kirsten; Oxenius, Annette; Regoes, Roland R. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2011)
Immune responses mediated by cytotoxic T lymphocytes (CTLs) have often been found to be functionally impaired in persistent infections. It is assumed that this impairment contributes to persistence of the infection. In this study, we compare the killing efficacy of CD8+ T-cell responses in mice acutely and persistently infected with the lymphocytic choriomeningitis virus, using an in vivo CTL killing assay. To infer the killing efficacy of CTLs, we developed a new mathematical model describing the disappearance of peptide-pulsed cells from the blood of the mice over time. We estimate a lower half-life for peptidepulsed cells in acute infection than in persistent infection, which indicates a higher killing efficacy of the CD8+ T-cell response in acute infection. However, by controlling for the different levels of CTLs in acutely and persistently infected mice, we find that CTLs in persistent infection are only two times less efficacious than CTLs in acute infections. These results strongly suggest that the in vivo cytotoxicity of CD8+ T-cell responses in persistent infection is modulated via the number of CTLs rather than their individual functionality. © 2011 The Royal Society.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Cellular immune response; Cytotoxic t lymphocyte efficacy; Mathematical modeling; Persistent infection; Population biology; Within host

Deciphering the triad of infection, immunity and pathology - Graw, Frederik (eLife, 2021)
CRIS-Team Scopus Importer:2022-12-14

Detection of signature double-negative T cells is a predictive marker to identify autoimmune lymphoproliferative syndrome associated with FAS loss of function - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Dell'Orso, Gianluca; Aigner, Michael; Fecker, Gisela; Hinze, Claas; Wittkowski, Helmut; Bruns, Heiko; Zierk, Jakob; Metzler, Markus; et al. (American Journal of Hematology, 2024)
CRIS-Team Scopus Importer:2024-03-29

Determining Ribavirin's mechanism of action against Lassa virus infection - Carrillo-Bustamante, Paola; Thi Huyen Tram Nguyen; Oestereich, Lisa; Guenther, Stephan; Guedj, Jeremie; Graw, Frederik (Scientific Reports, 2017)
Ribavirin is a broad spectrum antiviral which inhibits Lassa virus (LASV) replication in vitro but exhibits a minor effect on viremia in vivo. However, ribavirin significantly improves the disease outcome when administered in combination with sub-optimal doses of favipiravir, a strong antiviral drug. The mechanisms explaining these conflicting findings have not been determined, so far. Here, we used an interdisciplinary approach combining mathematical models and experimental data in LASV-infected mice that were treated with ribavirin alone or in combination with the drug favipiravir to explore different putative mechanisms of action for ribavirin. We test four different hypotheses that have been previously suggested for ribavirin's mode of action: (i) acting as a mutagen, thereby limiting the infectivity of new virions; (ii) reducing viremia by impairing viral production; (iii) modulating cell damage, i.e., by reducing inflammation, and (iv) enhancing antiviral immunity. Our analysis indicates that enhancement of antiviral immunity, as well as effects on viral production or transmission are unlikely to be ribavirin's main mechanism mediating its antiviral effectiveness against LASV infection. Instead, the modeled viral kinetics suggest that the main mode of action of ribavirin is to protect infected cells from dying, possibly reducing the inflammatory response.
CRIS-Team Scopus Importer:2022-12-14

Dynamic antibody specificities and virion concentrations in circulating immune complexes in acute to chronic HIV-1 infection - Liu, Pinghuang; Overman, R. Glenn; Yates, Nicole L.; Alam, S. Munir; Vandergrift, Nathan; Chen, Yue; Graw, Frederik; Freel, Stephanie A.; Kappes, John C.; Ochsenbauer, Christina; Montefiori, David C.; Gao, Feng; et al. (Journal of Virology, 2011)
Understanding the interactions between human immunodeficiency virus type 1 (HIV-1) virions and antibodies (Ab) produced during acute HIV-1 infection (AHI) is critical for defining antibody antiviral capabilities. Antibodies that bind virions may prevent transmission by neutralization of virus or mechanically prevent HIV-1 migration through mucosal layers. In this study, we quantified circulating HIV-1 virion-immune complexes (ICs), present in approximately 90% of AHI subjects, and compared the levels and antibody specificity to those in chronic infection. Circulating HIV-1 virions coated with IgG (immune complexes) were in significantly lower levels relative to the viral load in acute infection than in chronic HIV-1 infection. The specificities of the antibodies in the immune complexes differed between acute and chronic infection (anti-gp41 Ab in acute infection and anti-gp120 in chronic infection), potentially suggesting different roles in immunopathogenesis for complexes arising at different stages of infection. We also determined the ability of circulating IgG from AHI to bind infectious versus noninfectious virions. Similar to a nonneutralizing anti-gp41 monoclonal antibody (MAb), purified plasma IgG from acute HIV-1 subjects bound both infectious and noninfectious virions. This was in contrast to the neutralizing antibody 2G12 MAb that bound predominantly infectious virions. Moreover, the initial antibody response captured acute HIV-1 virions without selection for different HIV-1 envelope sequences. In total, this study demonstrates that the composition of immune complexes are dynamic over the course of HIV-1 infection and are comprised initially of antibodies that nonselectively opsonize both infectious and noninfectious virions, likely contributing to the lack of efficacy of the antibody response during acute infection. © 2011, American Society for Microbiology.
CRIS-Team Scopus Importer:2022-12-14

Dynamics of CD4+ T cell responses against Listeria monocytogenes - Graw, Frederik; Weber, K. Scott; Allen, Paul M.; Perelson, Alan S. (Journal of Immunology, 2012)
The generation of CD4+ T cell memory cells is poorly understood. Recently, two different murine CD4+ TCR transgenic T cell lines, LLO118 and LLO56, both specific for the same epitope but differing in their expression level of the cell surface protein CD5, were generated. Notably, these cell lines showed different behavior upon primary and secondary exposure to Listeria monocytogenes. Whereas LLO118 showed a stronger primary response and generated more robust CD8+ T cell help upon secondary exposure, LLO56 CD4+ T cells had a dramatically better recall response. Using different mathematical models, we analyzed the dynamics of the two CD4 + T cell lines in mice during infection with L. monocytogenes. Our models allowed the quantitative comparison of the two T cell lines and provided predictions for the conversion of naive T cells into memory cells. LLO118 CD4+ T cells are estimated to have a higher proliferation rate than LLO56 CD4+ T cells upon primary exposure. This difference can be explained by the lower expression level of CD5 on LLO118 CD4+ T cells. Furthermore, LLO56 memory cells are predicted to have a 3-fold longer half-life than LLO118 memory cells (t1/2LLO118 ≈ 4.3 to 5 d and t1/2LLO56 ≈ 11.5 to 13.9 d). Although both cell lines differ in their memory capabilities, our analysis indicates no difference in the rate at which memory cells are generated. Our results show that different CD5 expression levels influence the proliferation dynamics of activated naive CD4+ T cells while leaving the conversion rate of those cells into memory cells unaffected.
CRIS-Team Scopus Importer:2022-12-14

Early HCV viral kinetics under DAAs may optimize duration of therapy in patients with compensated cirrhosis - Gambato, Martina; Canini, Laetitia; Lens, Sabela; Graw, Frederik; Perpinan, Elena; Londono, Maria-Carlota; Uprichard, Susan L.; Marino, Zoe; Reverter, Enric; Bartres, Concepcio; Gonzalez, Patricia; Pla, Anna; et al. (Liver International, 2019)
Background & Aims: Detailed hepatitis C virus (HCV) kinetics modelling is scarce in patients with advanced liver disease receiving direct-acting antivirals (DAAs). Due to budget restrictions, patients and health systems would benefit from the shortest possible treatment course. We investigated whether modelling very early HCV kinetics in cirrhotic patients under DAAs therapy could be used to individualize care and reduce treatment duration to achieve cure. Methods: We included 74 patients with HCV-related cirrhosis who received interferon-free treatments for 12-24 weeks. HCV genotype, liver disease stage and treatment regimen were recorded. Viral load was determined prospectively at very frequent intervals until target not detected (TND, <15 IU/mL). A viral kinetic model was used to predict time to cure based on HCV clearance in extracellular body fluid (CL-EF). Results: Sixty-eight patients (92%) achieved cure. Thirteen (18%) had MELD ≥15, 35 (47%) were Child-Pugh (CTP) ≥7. Median time to reach TND was 2 weeks (IQR: 1-4 weeks). Modelling indicated an average DAAs efficacy in blocking viral production of ε = 99.1%. HCV half-life (t 1/2 ) was significantly shorter in patients with CTP <7, LSM <21 kPa or MELD <15 (1.5 vs 2.5 hours; P = 0.0057). The overall median CL-EF was 5.6 weeks (4.1-7.8). A CTP >7 and a LSM ≥21 kPa were significantly (P = 0.016) associated with longer CL-EF. Conclusions: The study provides insights into HCV dynamics during DAAs therapy in patients with compensated and decompensated cirrhosis. Viral kinetics modelling suggests that treatment duration may be optimized in patients with compensated cirrhosis.
CRIS-Team Scopus Importer:2022-12-14
Keywords: antivirals; hepatitis C; interferon-free; liver disease; mathematical modelling

Ebola virus dynamics in mice treated with favipiravir - Madelain, Vincent; Oestereich, Lisa; Graw, Frederik; Thi Huyen Tram Nguyen; De Lamballerie, Xavier; Mentre, France; Guenther, Stephan; Guedj, Jeremie (Antiviral Research, 2015)
The polymerase inhibitor favipiravir is a candidate for the treatment of Ebola virus disease. Here, we designed a mathematical model to characterize the viral dynamics in 20 mice experimentally infected with Ebola virus, which were either left untreated or treated with favipiravir at 6 or 8 days post infection. This approach provided estimates of kinetic parameters of Ebola virus reproduction, such as the half-life of productively infected cells, of about 6 h, and the basic reproductive number which indicates that virus produced by a single infected cell productively infects about 9 new cells. Furthermore, the model predicted that favipiravir efficiently blocks viral production, reaching an antiviral effectiveness of 95% and 99.6% at 2 and 6 days after initiation of treatment, respectively. The model could be particularly helpful to guide future studies evaluating favipiravir in larger animals.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Ebola; Favipiravir; Modeling; Viral kinetics

Environmental Restrictions: A New Concept Governing HIV-1 Spread Emerging from Integrated Experimental-Computational Analysis of Tissue-Like 3D Cultures - Ahmed, Samy Sid; Bundgaard, Nils; Graw, Frederik; Fackler, Oliver T. (Cells, 2020)
HIV-1 can use cell-free and cell-associated transmission modes to infect new target cells, but how the virus spreads in the infected host remains to be determined. We recently established 3D collagen cultures to study HIV-1 spread in tissue-like environments and applied iterative cycles of experimentation and computation to develop a first in silico model to describe the dynamics of HIV-1 spread in complex tissue. These analyses (i) revealed that 3D collagen environments restrict cell-free HIV-1 infection but promote cell-associated virus transmission and (ii) defined that cell densities in tissue dictate the efficacy of these transmission modes for virus spread. In this review, we discuss, in the context of the current literature, the implications of this study for our understanding of HIV-1 spread in vivo, which aspects of in vivo physiology this integrated experimental-computational analysis takes into account, and how it can be further improved experimentally and in silico.
CRIS-Team Scopus Importer:2022-12-14
Keywords: 3D cultures; cell-free infection; cell–cell transmission; environmental restriction; HIV-1 spread; mathematical modeling

Erratum: Theoretical analysis of the evolution of immune memory (BMC Evolutionary Biology (2011) 11 (54)) - Graw, Frederik; Magnus, Carsten; Regoes, Roland R. (BMC Evolutionary Biology, 2011)
CRIS-Team Scopus Importer:2022-12-14

Estimating the In Vivo Killing Efficacy of Cytotoxic T Lymphocytes across Different Peptide-MHC Complex Densities - Garcia, Victor; Richter, Kirsten; Graw, Frederik; Oxenius, Annette; Regoes, Roland R. (PLoS Computational Biology, 2015)
Cytotoxic T lymphocytes (CTLs) are important agents in the control of intracellular pathogens, which specifically recognize and kill infected cells. Recently developed experimental methods allow the estimation of the CTL's efficacy in detecting and clearing infected host cells. One method, the in vivo killing assay, utilizes the adoptive transfer of antigen displaying target cells into the bloodstream of mice. Surprisingly, killing efficacies measured by this method are often much higher than estimates obtained by other methods based on, for instance, the dynamics of escape mutations. In this study, we investigated what fraction of this variation can be explained by differences in peptide loads employed in in vivo killing assays. We addressed this question in mice immunized with lymphocytic choriomeningitis virus (LCMV). We conducted in vivo killing assays varying the loads of the immunodominant epitope GP33 on target cells. Using a mathematical model, we determined the efficacy of effector and memory CTL, as well as CTL in chronically infected mice. We found that the killing efficacy is substantially reduced at lower peptide loads. For physiological peptide loads, our analysis predicts more than a factor 10 lower CTL efficacies than at maximum peptide loads. Assuming that the efficacy scales linearly with the frequency of CTL, a clear hierarchy emerges among the groups across all peptide antigen concentrations. The group of mice with chronic LCMV infections shows a consistently higher killing efficacy per CTL than the acutely infected mouse group, which in turn has a consistently larger efficacy than the memory mouse group. We conclude that CTL killing efficacy dependence on surface epitope frequencies can only partially explain the variation in in vivo killing efficacy estimates across experimental methods and viral systems, which vary about four orders of magnitude. In contrast, peptide load differences can explain at most two orders of magnitude.
CRIS-Team Scopus Importer:2022-12-14

Examining the reticulocyte preference of two Plasmodium berghei strains during blood-stage malaria infection - Thakre, Neha; Fernandes, Priyanka; Mueller, Ann-Kristin; Graw, Frederik (Frontiers in Microbiology, 2018)
The blood-stage of the Plasmodium parasite is one of the key phases within its life cycle that influences disease progression during a malaria infection. The efficiency of the parasite in infecting red blood cells (RBC) determines parasite load and parasite-induced hemolysis that is responsible for the development of anemia and potentially drives severe disease progression. However, the molecular factors defining the infectivity of Plasmodium parasites have not been completely identified so far. Using the Plasmodium berghei mouse model for malaria, we characterized and compared the blood-stage infection dynamics of PbANKA WT and a mutant parasite strain lacking a novel Plasmodium antigen, PbmaLS_05, that is well conserved in both human and animal Plasmodium parasite strains. Infection of mice with parasites lacking PbmaLS_05 leads to lower parasitemia levels and less severe disease progression in contrast to mice infected with the wildtype PbANKA strain. To specifically determine the effect of deleting PbmaLS_05 on parasite infectivity we developed a mathematical model describing erythropoiesis and malarial infection of RBC. By applying our model to experimental data studying infection dynamics under normal and drug-induced altered erythropoietic conditions, we found that both PbANKA and PbmaLS_05 (-) parasite strains differed in their infectivity potential during the early intra-erythrocytic stage of infection. Parasites lacking PbmaLS_05 showed a decreased ability to infect RBC, and immature reticulocytes in particular that are usually a preferential target of the parasite. These altered infectivity characteristics limit parasite burden and affect disease progression. Our integrative analysis combining mathematical models and experimental data suggests that deletion of PbmaLS_05 affects productive infection of reticulocytes, which makes this antigen a useful target to analyze the actual processes relating RBC preferences to the development of severe disease outcomes in malaria.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Erythropoiesis; Infection dynamics; Malaria; Mathematical modeling; Parasite infectivity; Plasmodium

Experimental and computational analyses reveal that environmental restrictions shape HIV-1 spread in 3D cultures - Imle, Andrea; Kumberger, Peter; Schnellbaecher, Nikolas D.; Fehr, Jana; Carrillo-Bustamante, Paola; Ales, Janez; Schmidt, Philip; Ritter, Christian; Godinez, William J.; Mueller, Barbara; Rohr, Karl; Hamprecht, Fred A.; et al. (Nature Communications, 2019)
Pathogens face varying microenvironments in vivo, but suitable experimental systems and analysis tools to dissect how three-dimensional (3D) tissue environments impact pathogen spread are lacking. Here we develop an Integrative method to Study Pathogen spread by Experiment and Computation within Tissue-like 3D cultures (INSPECT-3D), combining quantification of pathogen replication with imaging to study single-cell and cell population dynamics. We apply INSPECT-3D to analyze HIV-1 spread between primary human CD4 T-lymphocytes using collagen as tissue-like 3D-scaffold. Measurements of virus replication, infectivity, diffusion, cellular motility and interactions are combined by mathematical analyses into an integrated spatial infection model to estimate parameters governing HIV-1 spread. This reveals that environmental restrictions limit infection by cell-free virions but promote cell-associated HIV-1 transmission. Experimental validation identifies cell motility and density as essential determinants of efficacy and mode of HIV-1 spread in 3D. INSPECT-3D represents an adaptable method for quantitative time-resolved analyses of 3D pathogen spread.
CRIS-Team Scopus Importer:2022-12-14

Extended methods for spatial cell classification with DBSCAN-CellX - Küchenhoff, Leonie; Lukas, Pascal; Metz-Zumaran, Camila; Rothhaar, Paul; Ruggieri, Alessia; Lohmann, Volker; Höfer, Thomas; Stanifer, Megan L.; Boulant, Steeve; Talemi, Soheil Rastgou; Graw, Frederik (Scientific Reports, 2023)
Local cell densities and positioning within cellular monolayers and stratified epithelia have important implications for cell interactions and the functionality of various biological processes. To analyze the relationship between cell localization and tissue physiology, density-based clustering algorithms, such as DBSCAN, allow for a detailed characterization of the spatial distribution and positioning of individual cells. However, these methods rely on predefined parameters that influence the outcome of the analysis. With varying cell densities in cell cultures or tissues impacting cell sizes and, thus, cellular proximities, these parameters need to be carefully chosen. In addition, standard DBSCAN approaches generally come short in appropriately identifying individual cell positions. We therefore developed three extensions to the standard DBSCAN-algorithm that provide: (i) an automated parameter identification to reliably identify cell clusters, (ii) an improved identification of cluster edges; and (iii) an improved characterization of the relative positioning of cells within clusters. We apply our novel methods, which are provided as a user-friendly OpenSource-software package (DBSCAN-CellX), to cellular monolayers of different cell lines. Thereby, we show the importance of the developed extensions for the appropriate analysis of cell culture experiments to determine the relationship between cell localization and tissue physiology.
CRIS-Team Scopus Importer:2023-11-24

FAMOS: A Flexible and dynamic Algorithm for Model Selection to analyse complex systems dynamics - Gabel, Michael; Hohl, Tobias; Imle, Andrea; Fackler, Oliver T.; Graw, Frederik (PLoS Computational Biology, 2019)
Most biological systems are difficult to analyse due to a multitude of interacting components and the concomitant lack of information about the essential dynamics. Finding appropriate models that provide a systematic description of such biological systems and that help to identify their relevant factors and processes can be challenging given the sheer number of possibilities. Model selection algorithms that evaluate the performance of a multitude of different models against experimental data provide a useful tool to identify appropriate model structures. However, many algorithms addressing the analysis of complex dynamical systems, as they are often used in biology, compare a preselected number of models or rely on exhaustive searches of the total model space which might be unfeasible dependent on the number of possibilities. Therefore, we developed an algorithm that is able to perform model selection on complex systems and searches large model spaces in a dynamical way. Our algorithm includes local and newly developed non-local search methods that can prevent the algorithm from ending up in local minima of the model space by accounting for structurally similar processes. We tested and validated the algorithm based on simulated data and showed its flexibility for handling different model structures. We also used the algorithm to analyse experimental data on the cell proliferation dynamics of CD4+ and CD8+ T cells that were cultured under different conditions. Our analyses indicated dynamical changes within the proliferation potential of cells that was reduced within tissue-like 3D ex vivo cultures compared to suspension. Due to the flexibility in handling various model structures, the algorithm is applicable to a large variety of different biological problems and represents a useful tool for the data-oriented evaluation of complex model spaces.
CRIS-Team Scopus Importer:2022-12-14

FitMultiCell: simulating and parameterizing computational models of multi-scale and multi-cellular processes - Alamoudi, Emad; Schälte, Yannik; Müller, Robert; Starruß, Jörn; Bundgaard, Nils; Graw, Frederik; Brusch, Lutz; Hasenauer, Jan (Bioinformatics (Oxford, England), 2023)
Motivation: Biological tissues are dynamic and highly organized. Multi-scale models are helpful tools to analyse and understand the processes determining tissue dynamics. These models usually depend on parameters that need to be inferred from experimental data to achieve a quantitative understanding, to predict the response to perturbations, and to evaluate competing hypotheses. However, even advanced inference approaches such as approximate Bayesian computation (ABC) are difficult to apply due to the computational complexity of the simulation of multi-scale models. Thus, there is a need for a scalable pipeline for modeling, simulating, and parameterizing multi-scale models of multi-cellular processes. Results: Here, we present FitMultiCell, a computationally efficient and user-friendly open-source pipeline that can handle the full workflow of modeling, simulating, and parameterizing for multi-scale models of multi-cellular processes. The pipeline is modular and integrates the modeling and simulation tool Morpheus and the statistical inference tool pyABC. The easy integration of high-performance infrastructure allows to scale to computationally expensive problems. The introduction of a novel standard for the formulation of parameter inference problems for multi-scale models additionally ensures reproducibility and reusability. By applying the pipeline to multiple biological problems, we demonstrate its broad applicability, which will benefit in particular image-based systems biology.
CRIS-Team Scopus Importer:2023-12-15

HCV kinetic and modeling analyses indicate similar time to cure among sofosbuvir combination regimens with daclatasvir, simeprevir or ledipasvir - Dahari, Harel; Canini, Laetitia; Graw, Frederik; Uprichard, Susan L.; Araujo, Evaldo S. A.; Penaranda, Guillaume; Coquet, Emilie; Chiche, Laurent; Riso, Aurelie; Renou, Christophe; Bourliere, Marc; Cotler, Scott J.; et al. (Journal of Hepatology, 2016)
Background & Aims Recent clinical trials of direct-acting-antiviral agents (DAAs) against hepatitis C virus (HCV) achieved >90% sustained virological response (SVR) rates, suggesting that cure often took place before the end of treatment (EOT). We sought to evaluate retrospectively whether early response kinetics can provide the basis to individualize therapy to achieve optimal results while reducing duration and cost. Methods 58 chronic HCV patients were treated with 12-week sofosbuvir + simeprevir (n = 19), sofosbuvir + daclatasvir (n = 19), or sofosbuvir + ledipasvir in three French referral centers. HCV was measured at baseline, day 2, every other week, EOT and 12 weeks post EOT. Mathematical modeling was used to predict the time to cure, i.e., <1 virus copy in the entire extracellular body fluid. Results All but one patient who relapsed achieved SVR. Mean age was 60 ± 11 years, 53% were male, 86% HCV genotype-1, 9% HIV coinfected, 43% advanced fibrosis (F3), and 57% had cirrhosis. At weeks 2, 4 and 6, 48%, 88% and 100% of patients had HCV <15 IU/ml, with 27%, 74% and 91% of observations having target not detected, respectively. Modeling results predicted that 23 (43%), 16 (30%), 7 (13%), 5 (9%) and 3 (5%) subjects were predicted to reach cure within 6, 8, 10, 12 and 13 weeks of therapy, respectively. The modeling suggested that the patient who relapsed would have benefitted from an additional week of sofosbuvir + ledipasvir. Adjusting duration of treatment according to the modeling predicts reduced medication costs of 43-45% and 17-30% in subjects who had HCV <15 IU/ml at weeks 2 and 4, respectively. Conclusions The use of early viral kinetic analysis has the potential to individualize duration of DAA therapy with a projected average cost saving of 16-20% per 100-treated persons.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Duration of therapy; HCV; Mathematical modeling; SVR; Viral kinetics

HCV spread kinetics reveal varying contributions of transmission modes to infection dynamics - Durso-Cain, Karina; Kumberger, Peter; Schaelte, Yannik; Fink, Theresa; Dahari, Harel; Hasenauer, Jan; Uprichard, Susan L.; Graw, Frederik (Viruses, 2021)
The hepatitis C virus (HCV) is capable of spreading within a host by two different transmission modes: cell-free and cell-to-cell. However, the contribution of each of these transmission mechanisms to HCV spread is unknown. To dissect the contribution of these different transmission modes to HCV spread, we measured HCV lifecycle kinetics and used an in vitro spread assay to monitor HCV spread kinetics after a low multiplicity of infection in the absence and presence of a neutralizing antibody that blocks cell-free spread. By analyzing these data with a spatially explicit mathematical model that describes viral spread on a single-cell level, we quantified the contribution of cell-free, and cell-to-cell spread to the overall infection dynamics and show that both transmission modes act synergistically to enhance the spread of infection. Thus, the simultaneous occurrence of both transmission modes represents an advantage for HCV that may contribute to viral persistence. Notably, the relative contribution of each viral transmission mode appeared to vary dependent on different experimental conditions and suggests that viral spread is optimized according to the environment. Together, our analyses provide insight into the spread dynamics of HCV and reveal how different transmission modes impact each other.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Agent-based model; Cell-to-cell transmission; HCV; Mathematical modeling; Spatial spread

HIV-1 replication activates CD4+ T cells with specificities for persistent herpes viruses - Haas, Anna; Rehr, Manuela; Graw, Frederik; Rusert, Peter; Bossart, Walter; Kuster, Herbert; Trkola, Alexandra; Guenthard, Huldrych F.; Oxenius, Annette (Embo Molecular Medicine, 2010)
Hyperactivation of CD4+ T cells is a hallmark of untreated HIV-1 infection. The antigenic specificities of activated CD4+ T cells and the underlying mechanisms leading to their activation remain thus far elusive. We report here that during HIV rebound the dynamics of HIV-specific CD4 + T cells is highly correlated with the dynamics of CD4+ T cells specific for persistent antigens derived from various members of the herpes virus family, whereas CD4 responses towards nonpersistent antigens were unaffected by HIV replication. Notably, the dynamics of HIV and herpes viral antigen-specific CD4+ T cells responses correlated with the expression level of activation markers on dendritic cells (DCs) and activated DCs were more potent in restimulating memory T cells. These data strongly suggest that HIV replication costimulates activation of CD4+ T cells specific for persistent herpes viral antigens via activation of DCs. We propose that a large proportion of activated T cells during untreated HIV infection may be specific for herpes viral antigens and identify a novel mechanism contributing to chronic immune activation in untreated HIV-1 infection. © 2010 EMBO Molecular Medicine.
CRIS-Team Scopus Importer:2022-12-14
Keywords: CD4+ T cells; Chronic immune activation; Dendritic cells; Herpes viruses; HIV pathogenesis

Inferring Viral Dynamics in Chronically HCV Infected Patients from the Spatial Distribution of Infected Hepatocytes - Graw, Frederik; Balagopal, Ashwin; Kandathil, Abraham J.; Ray, Stuart C.; Thomas, David L.; Ribeiro, Ruy M.; Perelson, Alan S. (PLoS Computational Biology, 2014)
Chronic liver infection by hepatitis C virus (HCV) is a major public health concern. Despite partly successful treatment options, several aspects of intrahepatic HCV infection dynamics are still poorly understood, including the preferred mode of viral propagation, as well as the proportion of infected hepatocytes. Answers to these questions have important implications for the development of therapeutic interventions. In this study, we present methods to analyze the spatial distribution of infected hepatocytes obtained by single cell laser capture microdissection from liver biopsy samples of patients chronically infected with HCV. By characterizing the internal structure of clusters of infected cells, we are able to evaluate hypotheses about intrahepatic infection dynamics. We found that individual clusters on biopsy samples range in size from (Formula presented.) infected cells. In addition, the HCV RNA content in a cluster declines from the cell that presumably founded the cluster to cells at the maximal cluster extension. These observations support the idea that HCV infection in the liver is seeded randomly (e.g. from the blood) and then spreads locally. Assuming that the amount of intracellular HCV RNA is a proxy for how long a cell has been infected, we estimate based on models of intracellular HCV RNA replication and accumulation that cells in clusters have been infected on average for less than a week. Further, we do not find a relationship between the cluster size and the estimated cluster expansion time. Our method represents a novel approach to make inferences about infection dynamics in solid tissues from static spatial data.
CRIS-Team Scopus Importer:2022-12-14

Influence of cell type specific infectivity and tissue composition on SARS-CoV-2 infection dynamics within human airway epithelium - Raach, Benjamin; Bundgaard, Nils; Haase, Marika J.; Starruß, Jörn; Sotillo, Rocio; Stanifer, Megan L.; Graw, Frederik (PLoS Computational Biology, 2023)
Human airway epithelium (HAE) represents the primary site of viral infection for SARS-CoV-2. Comprising different cell populations, a lot of research has been aimed at deciphering the major cell types and infection dynamics that determine disease progression and severity. However, the cell type-specific replication kinetics, as well as the contribution of cellular composition of the respiratory epithelium to infection and pathology are still not fully understood. Although experimental advances, including Air-liquid interface (ALI) cultures of reconstituted pseudostratified HAE, as well as lung organoid systems, allow the observation of infection dynamics under physiological conditions in unprecedented level of detail, disentangling and quantifying the contribution of individual processes and cells to these dynamics remains challenging. Here, we present how a combination of experimental data and mathematical modelling can be used to infer and address the influence of cell type specific infectivity and tissue composition on SARS-CoV-2 infection dynamics. Using a stepwise approach that integrates various experimental data on HAE culture systems with regard to tissue differentiation and infection dynamics, we develop an individual cell-based model that enables investigation of infection and regeneration dynamics within pseudostratified HAE. In addition, we present a novel method to quantify tissue integrity based on image data related to the standard measures of transepithelial electrical resistance measurements. Our analysis provides a first aim of quantitatively assessing cell type specific infection kinetics and shows how tissue composition and changes in regeneration capacity, as e.g. in smokers, can influence disease progression and pathology. Furthermore, we identified key measurements that still need to be assessed in order to improve inference of cell type specific infection kinetics and disease progression. Our approach provides a method that, in combination with additional experimental data, can be used to disentangle the complex dynamics of viral infection and immunity within human airway epithelial culture systems.
CRIS-Team Scopus Importer:2023-09-15

Influence of the fibroblastic reticular network on cell-cell interactions in lymphoid organs - Graw, Frederik; Regoes, Roland R. (PLoS Computational Biology, 2012)
Secondary lymphoid organs (SLO), such as lymph nodes and the spleen, display a complex micro-architecture. In the T cell zone the micro-architecture is provided by a network of fibroblastic reticular cells (FRC) and their filaments. The FRC network is thought to enhance the interaction between immune cells and their cognate antigen. However, the effect of the FRC network on cell interaction cannot be quantified to date because of limitations in immunological methodology. We use computational models to study the influence of different densities of FRC networks on the probability that two cells meet. We developed a 3D cellular automaton model to simulate cell movements and interactions along the FRC network inside lymphatic tissue. We show that the FRC network density has only a small effect on the probability of a cell to come into contact with a static or motile target. However, damage caused by a disruption of the FRC network is greatest at FRC densities corresponding to densities observed in the spleen of naïve mice. Our analysis suggests that the FRC network as a guiding structure for moving T cells has only a minor effect on the probability to find a corresponding dendritic cell. We propose alternative hypotheses by which the FRC network might influence the functionality of immune responses in a more significant way. © 2012 Graw, Regoes.
CRIS-Team Scopus Importer:2022-12-14

Investigating CTL mediated killing with a 3D cellular automaton - Graw, Frederik; Regoes, Roland R. (PLoS Computational Biology, 2009)
Cytotoxic T lymphocytes (CTLs) are important immune effectors against intra-cellular pathogens. These cells search for infected cells and kill them. Recently developed experimental methods in combination with mathematical models allow for the quantification of the efficacy of CTL killing in vivo and, hence, for the estimation of parameters that characterize the effect of CTL killing on the target cell populations. It is not known how these population-level parameters relate to single-cell properties. To address this question, we developed a three-dimensional cellular automaton model of the region of the spleen where CTL killing takes place. The cellular automaton model describes the movement of different cell populations and their interactions. Cell movement patterns in our cellular automaton model agree with observations from two-photon microscopy. We find that, despite the strong spatial nature of the kinetics in our cellular automaton model, the killing of target cells by CTLs can be described by a term which is linear in the target cell frequency and saturates with respect to the CTL levels. Further, we find that the parameters describing CTL killing on the population level are most strongly impacted by the time a CTL needs to kill a target cell. This suggests that the killing of target cells, rather than their localization, is the limiting step in CTL killing dynamics given reasonable frequencies of CTL. Our analysis identifies additional experimental directions which are of particular importance to interpret estimates of killing rates and could advance our quantitative understanding of CTL killing. © 2009 Graw, Regoes.
CRIS-Team Scopus Importer:2022-12-14

Investigating the dynamics of MCMV-specific CD8+ T cell responses in individual hosts - Gabel, Michael; Baumann, Nicolas S.; Oxenius, Annette; Graw, Frederik (Frontiers in Immunology, 2019)
Infection by Cytomegalovirus (CMV) is characterized by the massive expansion and continued maintenance of CMV-specific CD8+ T cells for certain CMV-derived peptides. This phenomenon called “memory inflation" has made CMV a primary target for the generation of T cell based vaccine vectors against various diseases. However, many aspects concerning the generation and maintenance of the inflationary CD8+ T cell response still remain to be resolved. In this study, we combined experimental data and mathematical models to analyze the dynamics of circulatory inflationary CD8+ T cells within individual mice infected by MCMV. Obtaining frequent measurements on the number and frequency of CMV-specific CD8+ T cells up to 70 days post infection, we find that mathematical models assuming differing viral stimuli during acute infection and the inflationary phase provide a better description for the observed dynamics than models relying on similar viral stimuli during both phases. In addition, our analysis allowed a detailed quantification of the different phases of memory inflation within individual mice (1st-expansion - contraction - 2nd expansion/maintenance) indicating remarkable consistency of the timing of these phases across mice, but considerable variation in the size of the individual responses between mice. Our analysis provides a first step toward generating a mechanistic framework for analyzing the generation and maintenance of inflationary CD8+ T cells while accounting for individual heterogeneity. Extending these analyses by incorporating measurements from additional compartments and more prolonged sampling will help to obtain a systematic and quantitative understanding of the factors regulating the process of memory inflation.
CRIS-Team Scopus Importer:2022-12-14
Keywords: CD8; Individual dynamics; Mathematical modeling; MCMV-infection; Memory inflation

Modeling Favipiravir Antiviral Efficacy Against Emerging Viruses: From Animal Studies to Clinical Trials - Madelain, Vincent; Mentre, France; Baize, Sylvain; Anglaret, Xavier; Laouenan, Cedric; Oestereich, Lisa; Nguyen, Thi Huyen Tram; Malvy, Denis; Piorkowski, Geraldine; Graw, Frederik; Guenther, Stephan; Raoul, Herve; et al. (CPT: Pharmacometrics and Systems Pharmacology, 2020)
In 2014, our research network was involved in the evaluation of favipiravir, an anti-influenza polymerase inhibitor, against Ebola virus. In this review, we discuss how mathematical modeling was used, first to propose a relevant dosing regimen in humans, and then to optimize its antiviral efficacy in a nonhuman primate (NHP) model. The data collected in NHPs were finally used to develop a model of Ebola pathogenesis integrating the interactions among the virus, the innate and adaptive immune response, and the action of favipiravir. We conclude the review of this work by discussing how these results are of relevance for future human studies in the context of Ebola virus, but also for other emerging viral diseases for which no therapeutics are available.
CRIS-Team Scopus Importer:2022-12-14

Modeling Viral Spread - Graw, Frederik; Perelson, Alan S. (Annual Review of Virology, 2016)
The way in which a viral infection spreads within a host is a complex process that is not well understood. Different viruses, such as human immunodeficiency virus type 1 and hepatitis C virus, have evolved different strategies, including direct cell-to-cell transmission and cell-free transmission, to spread within a host. To what extent these two modes of transmission are exploited in vivo is still unknown. Mathematical modeling has been an essential tool to get a better systematic and quantitative understanding of viral processes that are difficult to discern through strictly experimental approaches. In this review, we discuss recent attempts that combine experimental data and mathematical modeling in order to determine and quantify viral transmission modes. We also discuss the current challenges for a systems-level understanding of viral spread, and we highlight the promises and challenges that novel experimental techniques and data will bring to the field.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Agent-based models; Cell-free virus infection; Cell-to-cell infection; HCV; HIV; Mathematical modeling

More or less - On the influence of labelling strategies to infer cell population dynamics - Gabel, Michael; Regoes, Roland R.; Graw, Frederik (PLoS ONE, 2017)
The adoptive transfer of labelled cell populations has been an essential tool to determine and quantify cellular dynamics. The experimental methods to label and track cells over time range from fluorescent dyes over congenic markers towards single-cell labelling techniques, such as genetic barcodes. While these methods have been widely used to quantify cell differentiation and division dynamics, the extent to which the applied labelling strategy actually affects the quantification of the dynamics has not been determined so far. This is especially important in situations where measurements can only be obtained at a single time point, as e.g. due to organ harvest. To this end, we studied the appropriateness of various labelling strategies as characterised by the number of different labels and the initial number of cells per label to quantify cellular dynamics. We simulated adoptive transfer experiments in systems of various complexity that assumed either homoeostatic cellular turnover or cell expansion dynamics involving various steps of cell differentiation and proliferation. Re-sampling cells at a single time point, we determined the ability of different labelling strategies to recover the underlying kinetics. Our results indicate that cell transition and expansion rates are differently affected by experimental shortcomings, such as loss of cells during transfer or sampling, dependent on the labelling strategy used. Furthermore, uniformly distributed labels in the transferred population generally lead to more robust and less biased results than non-equal label sizes. In addition, our analysis indicates that certain labelling approaches incorporate a systematic bias for the identification of complex cell expansion dynamics.
CRIS-Team Scopus Importer:2022-12-14

Multiscale modeling of virus replication and spread - Kumberger, Peter; Frey, Felix; Schwarz, Ulrich S.; Graw, Frederik (FEBS letters, 2016)
Replication and spread of human viruses is based on the simultaneous exploitation of many different host functions, bridging multiple scales in space and time. Mathematical modeling is essential to obtain a systems-level understanding of how human viruses manage to proceed through their life cycles. Here, we review corresponding advances for viral systems of large medical relevance, such as human immunodeficiency virus-1 (HIV-1) and hepatitis C virus (HCV). We will outline how the combination of mathematical models and experimental data has advanced our quantitative knowledge about various processes of these pathogens, and how novel quantitative approaches promise to fill remaining gaps.
CRIS-Team Scopus Importer:2022-12-14
Keywords: HCV; HIV; mathematical modeling; quantitative viral dynamics; systems biology

On pseudo-values for regression analysis in competing risks models - Graw, Frederik; Gerds, Thomas A.; Schumacher, Martin (Lifetime Data Analysis, 2009)
For regression on state and transition probabilities in multi-state models Andersen et al. (Biometrika 90:15-27, 2003) propose a technique based on jackknife pseudo-values. In this article we analyze the pseudo-values suggested for competing risks models and prove some conjectures regarding their asymptotics (Klein and Andersen, Biometrics 61:223-229, 2005). The key is a second order von Mises expansion of the Aalen-Johansen estimator which yields an appropriate representation of the pseudo-values. The method is illustrated with data from a clinical study on total joint replacement. In the application we consider for comparison the estimates obtained with the Fine and Gray approach (J Am Stat Assoc 94:496-509, 1999) and also time-dependent solutions of pseudo-value regression equations. © 2008 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Competing risks; Generalized estimating equation; Jackknife pseudo-values; Regression models; Survival analysis; Von Mises expansion

OutbreakFlow: Model-based Bayesian inference of disease outbreak dynamics with invertible neural networks and its application to the COVID-19 pandemics in Germany - Radev, Stefan T.; Graw, Frederik; Chen, Simiao; Mutters, Nico T.; Eichel, Vanessa M.; Baernighausen, Till; Koethe, Ullrich (PLoS Computational Biology, 2021)
Mathematical models in epidemiology are an indispensable tool to determine the dynamics and important characteristics of infectious diseases. Apart from their scientific merit, these models are often used to inform political decisions and interventional measures during an ongoing outbreak. However, reliably inferring the epidemical dynamics by connecting complex models to real data is still hard and requires either laborious manual parameter fitting or expensive optimization methods which have to be repeated from scratch for every application of a given model. In this work, we address this problem with a novel combination of epidemiological modeling with specialized neural networks. Our approach entails two computational phases: In an initial training phase, a mathematical model describing the epidemic is used as a coach for a neural network, which acquires global knowledge about the full range of possible disease dynamics. In the subsequent inference phase, the trained neural network processes the observed data of an actual outbreak and infers the parameters of the model in order to realistically reproduce the observed dynamics and reliably predict future progression. With its flexible framework, our simulation-based approach is applicable to a variety of epidemiological models. Moreover, since our method is fully Bayesian, it is designed to incorporate all available prior knowledge about plausible parameter values and returns complete joint posterior distributions over these parameters. Application of our method to the early Covid-19 outbreak phase in Germany demonstrates that we are able to obtain reliable probabilistic estimates for important disease characteristics, such as generation time, fraction of undetected infections, likelihood of transmission before symptom onset, and reporting delays using a very moderate amount of real-world observations.
CRIS-Team Scopus Importer:2022-12-14

Post-treatment human papillomavirus antibody kinetics in cervical cancer patients - Piontek, Till; Harmel, Christoph; Pawlita, Michael; Carow, Katrin; Schroeter, Juliane; Runnebaum, Ingo B.; Duerst, Matthias; Graw, Frederik; Waterboer, Tim (Philosophical Transactions of the Royal Society B-Biological Sciences, 2019)
Antibodies to the E6 and E7 oncoproteins of high-risk human papillomavirus (HPV) types are strongly associated with HPV-driven cancer, while antibodies against the capsid protein L1 are considered cumulative exposure markers. To test the hypothesis that L1 antibody levels are stable over time, whereas E6 and E7 levels undergo decay after cervical cancer (CxCa) treatment, we performed multiplex serology for HPV16 and 18 antigens E6, E7 and L1 in a post-treatment study of 184 patients with invasive CxCa that were characterized with a median follow-up time of 725 days, and 2 - 12 sera per patient. Antibody titers significantly decreased within the first six months for HPV16 E6 and E7 but not L1, and stabilized for the following 12 months on a high level, with few patients showing seroreversion. Of 67 patients seropositive for HPV16 E6 at diagnosis, 28 (41.8%) showed a decrease in antibody titers of at least 50% within the first 18 months. Similarly, of 50 HPV16 E7 seropositives, 33 (66.0%) showed decreasing antibody levels, whereas antibody decay was less frequent for HPV16 L1 (12 of 47, 25.5%). Using a power-law mathematical model to characterize antibody decay kinetics, the mean (+s.e.) durations to a 50% reduction in antibody titers within individual patients were estimated to be 56.9 (+26.1) and 56.3 (+19.0) days for HPV16 E6 and E7, respectively. In summary, HPV16 E6 and E7 antibodies undergo a slow but significant decrease in antibody titers within the first 6 - 18 months following CxCa treatment. However, larger studies are needed to confirm the utility of serology for prediction of disease progression and time to relapse based on antibody decay kinetics. This article is part of the theme issue 'Silent cancer agents: multidisciplinary modelling of human DNA oncoviruses'.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Antibody; Cervical cancer; Decay; Human papillomavirus; Kinetics; Mathematical modelling; Serology

Predicting the impact of CD8+ T cell polyfunctionality on HIV disease progression - Graw, Frederik; Regoes, Roland R. (Journal of Virology, 2014)
During the chronic phase of HIV-1 infection, polyfunctional CD8+ T cell responses, which are characterized by a high frequency of cells able to secrete multiple cytokines simultaneously, are associated with lower virus loads and slower disease progression. This relationship may arise for different reasons. Polyfunctional responses may simply be stronger. Alternatively, it could be that the increased functional diversity in polyfunctional responses leads to lower virus loads and slower disease progression. Lastly, polyfunctional responses could contain more CD8+ T cells that mediate a specific key function that is primarily responsible for viral control. Disentangling the influences of overall strength, functional diversity, and specific function on viral control and disease progression is very relevant for the rational design of vaccines and immunotherapy using cellular immune responses. We developed a mathematical model to study how polyfunctional CD8+ T cell responses mediating lytic and nonlytic effector functions affect the CD4+ T cell count and plasma viral load. We based our model on in vitro data on the efficacy of gamma interferon (IFN-γ) and macrophage inflammatory protein 1β (MIP-1β)/RANTES against HIV. We find that the strength of the response is a good predictor of disease progression, while functional diversity has only a minor influence. In addition, our model predicts for realistic levels of cytotoxicity that immune responses dominated by nonlytic effector functions most positively influence disease outcome.
CRIS-Team Scopus Importer:2022-12-14

Protective efficacy of individual CD8+ T cell specificities in chronic viral infection - Johnson, Susan; Bergthaler, Andreas; Graw, Frederik; Flatz, Lukas; Bonilla, Weldy V.; Siegrist, Claire-Anne; Lambert, Paul-Henri; Regoes, Roland R.; Pinschewer, Daniel D. (Journal of Immunology, 2015)
Specific CD8+ T cells (CTLs) play an important role in resolving protracted infection with hepatitis B and C virus in humans and lymphocytic choriomeningitis virus (LCMV) in mice. The contribution of individual CTL specificities to chronic virus control, as well as epitope-specific patterns in timing and persistence of antiviral selection pressure, remain, however, incompletely defined. To monitor and characterize the antiviral efficacy of individual CTL specificities throughout the course of chronic infection, we coinoculated mice with a mixture of wild-type LCMV and genetically engineered CTL epitope-deficient mutant virus. A quantitative longitudinal assessment of viral competition revealed that mice continuously exerted CTL selection pressure on the persisting virus population. The timing of selection pressure characterized individual epitope specificities, and its magnitude varied considerably between individual mice. This longitudinal assessment of "antiviral efficacy" provides a novel parameter to characterize CTL responses in chronic viral infection. It demonstrates remarkable perseverance of all antiviral CTL specificities studied, thus raising hope for therapeutic vaccination in the treatment of persistent viral diseases.
CRIS-Team Scopus Importer:2022-12-14

Quantification of hepatitis C virus cell-to-cell spread using a stochastic modeling approach - Graw, Frederik; Martin, Danyelle N.; Perelson, Alan S.; Uprichard, Susan L.; Dahari, Harel (Journal of Virology, 2015)
It has been proposed that viral cell-to-cell transmission plays a role in establishing and maintaining chronic infections. Thus, understanding the mechanisms and kinetics of cell-to-cell spread is fundamental to elucidating the dynamics of infection and may provide insight into factors that determine chronicity. Because hepatitis C virus (HCV) spreads from cell to cell and has a chronicity rate of up to 80% in exposed individuals, we examined the dynamics of HCV cell-to-cell spread in vitro and quantified the effect of inhibiting individual host factors. Using a multidisciplinary approach, we performed HCV spread assays and assessed the appropriateness of different stochastic models for describing HCV focus expansion. To evaluate the effect of blocking specific host cell factors on HCV cell-to-cell transmission, assays were performed in the presence of blocking antibodies and/or small-molecule inhibitors targeting different cellular HCV entry factors. In all experiments, HCV-positive cells were identified by immunohistochemical staining and the number of HCV-positive cells per focus was assessed to determine focus size. We found that HCV focus expansion can best be explained by mathematical models assuming focus size-dependent growth. Consistent with previous reports suggesting that some factors impact HCV cell-to-cell spread to different extents, modeling results estimate a hierarchy of efficacies for blocking HCV cell-to-cell spread when targeting different host factors (e.g., CLDN1 > NPC1L1 > TfR1). This approach can be adapted to describe focus expansion dynamics under a variety of experimental conditions as a means to quantify cell-to-cell transmission and assess the impact of cellular factors, viral factors, and antivirals. IMPORTANCE: The ability of viruses to efficiently spread by direct cell-to-cell transmission is thought to play an important role in the establishment and maintenance of viral persistence. As such, elucidating the dynamics of cell-to-cell spread and quantifying the effect of blocking the factors involved has important implications for the design of potent antiviral strategies and controlling viral escape. Mathematical modeling has been widely used to understand HCV infection dynamics and treatment response; however, these models typically assume only cell-free virus infection mechanisms. Here, we used stochastic models describing focus expansion as a means to understand and quantify the dynamics of HCV cell-to-cell spread in vitro and determined the degree to which cellto- cell spread is reduced when individual HCV entry factors are blocked. The results demonstrate the ability of this approach to recapitulate and quantify cell-to-cell transmission, as well as the impact of specific factors and potential antivirals.
CRIS-Team Scopus Importer:2022-12-14

SARS-CoV-2 variants of concern display enhanced intrinsic pathogenic properties and expanded organ tropism in mouse models - Stolp, Bettina; Stern, Marcel; Ambiel, Ina; Hofmann, Katharina; Morath, Katharina; Gallucci, Lara; Cortese, Mirko; Bartenschlager, Ralf; Ruggieri, Alessia; Graw, Frederik; Rudelius, Martina; Keppler, Oliver Till; et al. (Cell Reports, 2022)
SARS-CoV-2 variants of concern (VOCs) display enhanced transmissibility and resistance to antibody neutralization. Comparing the early 2020 isolate EU-1 to the VOCs Alpha, Beta, and Gamma in mice transgenic for human ACE2 reveals that VOCs induce a broadened scope of symptoms, expand systemic infection to the gastrointestinal tract, elicit the depletion of natural killer cells, and trigger variant-specific cytokine production patterns. Gamma infections result in accelerated disease progression associated with increased immune activation and inflammation. All four SARS-CoV-2 variants induce pDC depletion in the lungs, paralleled by reduced interferon responses. Remarkably, VOCs also use the murine ACE2 receptor for infection to replicate in the lungs of wild-type animals, which induce cellular and innate immune responses that apparently curtail the spread of overt disease. VOCs thus display distinct intrinsic pathogenic properties with broadened tissue and host range. The enhanced pathogenicity of VOCs and their potential for reverse zoonotic transmission pose challenges to clinical and pandemic management.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Alpha variant; Beta variant; cellular immunity; cytokine production; Gamma variant; ISG expression; K18-hACE2; SARS-CoV-2; variants of concern

Systemic antibody responses to gut commensal bacteria during chronic HIV-1 infection - Haas, Anna; Zimmermann, Kathrin; Graw, Frederik; Slack, Emma; Rusert, Peter; Ledergerber, Bruno; Bossart, Walter; Weber, Rainer; Thurnheer, Maria C.; Battegay, Manuel; Hirschel, Bernard; Vernazza, Pietro; et al. (Gut, 2011)
Background: Human systemic antibody responses to commensal microbiota are not well characterised during health and disease. Of particular interest is the analysis of their potential modulation caused by chronic HIV-1 infection which is associated with sustained enteropathy and systemic B cell disturbances reflected by impaired B cell responses and chronic B cell hyperactivity. The mechanisms underlying B cell hyperactivation and the specificities of the resulting hypergammaglobulinaemia are only poorly understood. Methods: By a technique referred to as live bacterial FACS (fluorescence-activated cell sorting), the present study investigated systemic antibody responses to several gut and skin commensal bacteria as well as Candida albicans in longitudinal plasma and serum samples from healthy donors, chronic HIV-1-infected individuals with or without diarrhoea and patients with inflammatory bowel disease (IBD). Results: The data show that systemic antibody responses to the commensal microbiota were abundantly present in humans and remained remarkably stable over years. Overall systemic antibody responses to gut commensal bacteria were not affected during chronic HIV-1 infection, with titres decreasing when normalised to elevated plasma immunoglobulin G (IgG) levels found in patients with HIV. In contrast, increases in the titres of high affinity antimicrobiota antibodies were detected in patients with IBD, demonstrating that conditions with known increased intestinal permeability and aberrant mutualism can induce changes in antibody titres observed in these assays. Conclusion: Neither HIV-associated enteropathy nor B cell dysfunction impact on the high-affinity systemic antibody responses to gut commensal bacteria. HIV-associated hypergammaglobulinaemia is therefore unlikely to be driven by induction of antimicrobiota antibodies.
CRIS-Team Scopus Importer:2022-12-14

TAT-CRE inhalation enables tumor induction corresponding to adenoviral Cre-recombinase in a lung cancer mouse model - Gewalt, Tabea; Dmitrieva, Anna M.; Elsner, Felix; Zhao, Xinlei; Sieber, Daniel Dimitri; Kocak, Ilayda Gülsen; Yang, Qian; Orschel, Claudia Viktoria; Eckert, Naja Maria; Goebel, Bianca; Nill, Marieke; Peter, Fiona; et al. (Communications Biology, 2025)
Cre-recombinase inducible model systems are extensively used in cancer research to manipulate gene expression in specific tissues and induce autochthonous tumor growth. These systems often involve the cross-breeding of genetically engineered organisms containing loxP-flanked alleles with those expressing Cre-recombinase. This approach, while effective, has the challenge of requiring high numbers of animals due to breeding requirements. Other frequently used tumor induction methods in cancer research involve the direct application of viral Cre-recombinase vectors. This approach presents the challenge of the accessibility of facilities that meet the necessary safety level. In this context, we perform a comprehensive comparison between TAT-CRE (biosafety level S1) and adenoviral Cre-recombinase induced (biosafety level S2) lung adenocarcinomas driven by KrasG12D expression and Trp53 depletion. We use in vivo lung tumor monitoring via computed tomography, single-cell RNA sequencing, immunohistochemistry and flow cytometry to elucidate similarities and differences between TAT-CRE and adenoviral Cre-recombinase induced lung adenocarcinomas. TAT-CRE induced lung tumors present differences in micro-vessels and macrophages but with corresponding tumor onset and growth characteristics compared to adenoviral-Cre recombinase induced lung tumors. Taken together, TAT-CRE is a valuable genetic engineering safety level S1 alternative for cancer induction and may be implemented in other cancer models than lung cancer.
CRIS-Team Scopus Importer:2025-05-23

Theoretical analysis of the evolution of immune memory - Graw, Frederik; Magnus, Carsten; Regoes, Roland R. (BMC Evolutionary Biology, 2010)
Background. The ability of an immune system to remember pathogens improves the chance of the host to survive a second exposure to the same pathogen. This immunological memory has evolved in response to the pathogen environment of the hosts. In vertebrates, the memory of previous infection is physiologically accomplished by the development of memory T and B cells. Many questions concerning the generation and maintenance of immunological memory are still debated. Is there a limit to how many memory cells a host can generate and maintain? If there is a limit, how should new cells be incorporated into a filled memory compartment? And how many different pathogens should the immune system remember?. Results. In this study, we examine how memory traits evolve as a response to different pathogen environments using an individual-based model. We find that even without a cost related to the maintenance of a memory pool, the positive effect of bigger memory pool sizes saturates. The optimal diversity of a limited memory pool is determined by the probability of re-infection, rather than by the prevalence of a pathogen in the environment, or the frequency of exposure. Conclusions. Relating immune memory traits to the pathogen environment of the hosts, our population biological framework sheds light on the evolutionary determinants of immune memory. © 2010 Graw et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-12-14

The population context is a driver of the heterogeneous response of epithelial cells to interferons - Metz-Zumaran, Camila; Uckeley, Zina M.; Doldan, Patricio; Muraca, Francesco; Keser, Yagmur; Lukas, Pascal; Kuropka, Benno; Küchenhoff, Leonie; Rastgou Talemi, Soheil; Höfer, Thomas; Freund, Christian; Cavalcanti-Adam, Elisabetta Ada; et al. (Molecular Systems Biology, 2024)
(Figure presented.) The heterogeneous response to interferons in epithelial cells is determined by the population context (i.e. a cell’s positions within a population) through cell polarization and basolateral localization of the interferon receptor. Isogenic epithelial cells respond in a heterogeneous manner to type I and type III interferons. The population context (position of a cell within a population) drives the heterogeneous response to interferons, with cells located at the edge of a population being more responsive than cells located in the center of a population. Cells in the center of a population are refractive to interferon treatment from their apical side due to the polarized basolateral distribution of the interferon receptors. By controlling the response to interferon treatment, the population context affects susceptibility to viral infection.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Epithelium; Heterogeneity; Interferons; Polarity; Population Context

Use of laser capture microdissection to map hepatitis C virus-positive hepatocytes in human liver - Kandathil, Abraham J.; Graw, Frederik; Quinn, Jeffrey; Hwang, Hyon S.; Torbenson, Michael; Perelson, Alan S.; Ray, Stuart C.; Thomas, David L.; Ribeiro, Ruy M.; Balagopal, Ashwin (Gastroenterology, 2013)
Background & Aims Hepatitis C virus (HCV) predominantly infects hepatocytes, but many hepatocytes are not infected; studies have shown that HCV antigens cluster within the liver. We investigated spatial distribution and determinants of HCV replication in human liver samples. Methods We analyzed liver samples from 4 patients with chronic HCV infection (genotype 1, Metavir scores 0-1) to estimate the proportion of infected hepatocytes and the amount of HCV viral RNA (vRNA) per cell. Single-cell laser capture microdissection was used to capture more than 1000 hepatocytes in grids, to preserve geometric relationships. HCV vRNA and interferon-induced transmembrane protein 3 (IFITM3) messenger RNA (the transcript of an interferon-stimulated gene) were measured in the same hepatocytes by quantitative polymerase chain reaction and assembled in maps to identify areas of high and low HCV replication. Results Patients' serum levels of HCV RNA ranged from 6.87 to 7.40 log10 IU/mL; the proportion of HCV-infected hepatocytes per person ranged from 21% to 45%, and the level of vRNA ranged from 1 to 50 IU/hepatocyte. Infection was not random; we identified clustering of HCV-positive hepatocytes using infected-neighbor analysis (P <.0005) and distance to the kth nearest neighbor compared with random distributions, obtained by bootstrap simulations (P <.02). Hepatocytes that expressed IFITM3 did not appear to cluster and were largely HCV negative. Conclusions We used single-cell laser capture and high-resolution analysis to show that in human liver HCV infects hepatocytes in nonrandom clusters, whereas expression of antiviral molecules is scattered among hepatocytes. These findings show that quantitative single-cell RNA measurements can be used to estimate the abundance of HCV vRNA per infected human hepatocyte and are consistent with cell-cell propagation of infection in the absence of clustered IFITM3. © 2013 by the AGA Institute.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Intrahepatic Infection; ISG; scLCM; Virology

Varying immunizations with Plasmodium radiation-attenuated sporozoites alter tissue-specific CD8+ T cell dynamics - Frank, Roland; Gabel, Michael; Heiss, Kirsten; Mueller, Ann-Kristin; Graw, Frederik (Frontiers in Immunology, 2018)
Whole sporozoite vaccines represent one of the most promising strategies to induce protection against malaria. However, the development of efficient vaccination protocols still remains a major challenge. To understand how the generation of immunity is affected by variations in vaccination dosage and frequency, we systematically analyzed intrasplenic and intrahepatic CD8+ T cell responses following varied immunizations of mice with radiation-attenuated sporozoites. By combining experimental data and mathematical modeling, our analysis indicates a reversing role of spleen and liver in the generation of protective liver-resident CD8+ T cells during priming and booster injections: While the spleen acts as a critical source compartment during priming, the increase in vaccine-induced hepatic T cell levels is likely due to local reactivation in the liver in response to subsequent booster injections. Higher dosing accelerates the efficient generation of liver-resident CD8+ T cells by especially affecting their local reactivation. In addition, we determine the differentiation and migration pathway from splenic precursors toward hepatic memory cells thereby presenting a mechanistic framework for the impact of various vaccination protocols on these dynamics. Thus, our work provides important insights into organ-specific CD8+ T cell dynamics and their role and interplay in the formation of protective immunity against malaria.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Experimental vaccination; Liver-resident CD8; Malaria; Mathematical modeling; Plasmodium berghei; Radiation-attenuated sporozoites

VisuStatR: Visualizing motility and morphology statistics on images in R - Harmel, Christoph; Ahmed, Samy Sid; Koch, Robin; Tunnermann, Jana; Distler, Tania; Imle, Andrea; Giorgetti, Luca; Bahn, Emanuel; Fackler, Oliver T.; Graw, Frederik (Bioinformatics, 2022)
Motivation: Live-cell microscopy has become an essential tool for analyzing dynamic processes in various biological applications. Thereby, high-throughput and automated tracking analyses allow the simultaneous evaluation of large numbers of objects. However, to critically assess the influence of individual objects on calculated summary statistics, and to detect heterogeneous dynamics or possible artifacts, such as misclassified or-tracked objects, a direct mapping of gained statistical information onto the actual image data would be necessary. Results: We present VisuStatR as a platform independent software package that allows the direct visualization of time-resolved summary statistics of morphological characteristics or motility dynamics onto raw images. The software contains several display modes to compare user-defined summary statistics and the underlying image data in various levels of detail.
CRIS-Team Scopus Importer:2022-12-14